Studies of Chemical Contamination and Toxic Pollutants in West Delhi-India - Ahmad, Anwar; Alam, Masood (Asian Journal of Chemistry, 2010)
The high urbanization and industrial growth rate in Delhi city have made it one of the most densely populated regions of India. This has resulted in an increase in the levels of environmental pollution from uncontrolled industrial effluents. The field investigation of chemical contaminants (Hg, Cd, Cr, Pb, Ni, Fe and Zn) and pesticides parameter were determined in underground water, drains, Yamuna river, aquatic plants and soils during the seasons (July–December) of 2001-2002. Nine samples of each reference sample and underground water samples, soils attached aquatic plant samples were collected from Yamuna river, near industrial effluent discharges along 35 km of located surface streams and drains which receive effluents from three major industrial areas. Contents of most parts of metals in soils, water and aquatic plants significantly correlated with each other and either a significant stimulatory or inhibitory effect on seedling plants. A variety of inorganic and organic analytes were detected in river soils and aquatic plants. Toxicity occurred downstream at 5 of the 6 sampling stations based on phytotoxivity and physical appearance of plants and invertebrate survival. The concentration of Hg is higher in drains and underground water found to be 21.5 and 1.5 μg/L respectively.